Avaliação de marcadores ósseos e sinal insulínico em ratas ovariectomizadas tratadas com fluoreto de sódio - Pereira, Amanda Gomes [UNESP] (2016)
Fluoride is an essential trace element for the maintenance of bone health due its capacity of stimulating the proliferation and osteoblastic activity that can lead to increase bone formation. However, excessive sodium fluoride intake can impair carbohydrate metabolism, promoting hyperglycemia, insulin resistance and change in insulin signal. Thus, this study aimed to evaluate the effect of chronic treatment with NaF in bone metabolism; insulin signaling; plasma concentrations of glucose, insulin, TNF-α, osteocalcin and fluoride in ovariectomized rats. Thirty six ovariectomized Wistar rats were randomly distributed into two groups: OVX-C, as control group, and OVX-F group, undergoing treatment with NaF (50mg F/L) in drinking water for 42 days. Plasma concentration of glucose and insulin were assessed, followed by homeostasis model assessment of insulin resistance (HOMA-IR). The Akt serine phosphorylation was evaluated by western blotting. The right and left tibias were collected for immunohistochemical and histomorphometric analysis, respectively. The chronic treatment with NaF promoted insulin resistance; decreased insulin signal; increase in the plasma concentration of insulin, fluoride, osteocalcin and TNF-α; decreased trabecular bone area of the tibia and changes in bone metabolism markers in ovariectomized rats. These results suggest caution in the use of NaF for the treatment of osteoporosis especially in postmenopausal woman.